As contribuições do uso das TDIC para o ensino superior - Piragibe, João Pedro Lacerda Salviano (2016)
This study aimed to analyze the contributions of Digital Technologies of Information and Communication (TDIC) for higher education teaching. To support the research, we had access to many authors cited in bilbiográficas references that address issues relevant to our work. Among them, we highlight for axes, which are Axis Education and Training: Maria da Graça Nicoletti Mizukami, Lee Schulman and Cristóbal Cobo Romani; Axis Training and Technology Education: Marcos Masetto, William John Thomas Mitchell and Lucia Santaella; and the last Axis Culture and Journalism: Henry Jenkins, Marshall McLuhan and Manuel Castells.O work also included the collaboration of four teachers of a private institution of higher education in the State of São Paulo (IPESESP), through interviews with semi-structured script , teachers those who work in the communications field, especially using the TDIC. research axes have been defined to better understand the results, among which we mention: The use of TDIC as a tool and strategy, reason for doing so, the institution's incentive for the use of technology and how to use TDIC for teaching in Journalism course. The choice of qualitative research took place in the character role of research and the established objectives. The big challenge we found was the lack of preparation even teachers to monitor their students, while noting that the use of technology is beneficial for students and teachers, provided that the parties were prepared to use. Through literature review found a need for teacher trainers, for the skilful and effective exercise of teaching, including using technological tools, the need is greater in the journalism course. The results observed through our interviews showed a general need for better preparation, and the professors of the University IPESESP are qualified for their roles, particularly regarding the use of the technological tools that use to use in teaching and learning. Their experiences are positive in the use of TDIC, and there is improvement in the quality of education, where technological tools are used appropriately.